Harmonization of RBSP and Arase Energetic Electron Measurements Utilizing ESA Radiation Monitor Data - Ingmar Sandberg; Piers Jiggens; Hugh Evans; Constantinos Papadimitriou; Sigiava Aminalragia‐Giamini; Christos Katsavrias; Alexander J. Boyd; Thomas Paul O’Brien; Nana Higashio; Takefumi Mitani; Iku Shinohara; Yoshizumi Miyoshi; et al. (Space Weather)
Abstract Accurate measurements of trapped energetic electron fluxes are of major importance for the studies of the complex nature of radiation belts and the characterization of space radiation environment. The harmonization of measurements between different instruments increases the accuracy of scientific studies and the reliability of data‐driven models that treat the specification of space radiation environment. An intercalibration analysis of the energetic electron flux measurements of the Magnetic Electron Ion Spectrometer (MagEIS) and the Relativistic Electron‐Proton Telescope (REPT) instruments on‐board the Van Allen Probes (VAP) Mission versus the measurements of the Extremely High Energy Electron Experiment (XEP) unit on‐board Arase satellite is presented. The performed analysis demonstrates a remarkable agreement between the majority of MagEIS and XEP measurements and suggests the rescaling of MagEIS HIGH unit and of REPT measurements for the treatment of flux spectra discontinuities. The proposed adjustments were validated successfully using measurements from ESA Environmental Monitoring Unit (EMU) on‐board GSAT0207 and the Standard Radiation Monitor (SREM) on‐board INTEGRAL. The derived results lead to the harmonization of science‐class experiments on‐board VAP (2012–2019) and Arase (2017–) and propose the use of the data sets as reference in a series of space weather and space radiation environment developments.